Pengaruh Penggunaan Limbah Masker Medis dan Limbah Serabut Kelapa sebagai Substitusi Pasir dalam Pembuatan Bata Ringan - Arroikhaanunnisa, Dini; Kusumawati, Nema Oryza; H, Hartono; Fauziyah, Shifa (Universitas Diponegoro, 2023)
Lightweight brick is a type of lightweight brick that is superior to the previous one. The purpose of this study was to analyze variations in the optimal composition of lightweight bricks (CLC) innovation by utilizing medical mask waste and coconut fiber waste as a substitute for sand based on bulk density and water absorption, compressive strength test, and soundproof test. The method used is the experimental method. Test object with variations in composition, namely 0%, 5%, 10% and 15%. Each variation has 3 samples with a total of 12. The values for bulk density and water absorption are in accordance with SNI 8640-2018. The compressive strength test was carried out using a cube specimen with a side of 15 cm aged 14 days. Soundproof test using a sound level meter. The results obtained at 10% variation with a mixture of 10% medical mask waste and 10% coconut fiber waste are the optimal composition in the manufacture of innovative lightweight bricks. The bulk density and water absorption were 0.0741%, the compressive strength test was 11.86 MPa, and the soundproof test was 24.3 dB. This lightweight brick innovation of 10% variation can be an alternative to smart, environmentally friendly and economical building materials.Keywords : Lightweight Brick (CLC), Medical Mask Waste, Coconut Fiber Waste, Content weight and Water absorption, Compressive Strength Test, Soundproofing Test